2015
DOI: 10.1016/j.vph.2015.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Optogenetic approach for functional assays of the cardiovascular system by light activation of the vascular smooth muscle

Abstract: Cardiovascular diseases are the major challenge to modern medicine. Intervention to cardiovascular cells is crucial for treatment of the diseases. Here we report a novel intervention to vascular smooth muscle (VSM) cells by optogenetics. Channelrhodopsin in a tandem with YFP was selectively expressed in smooth muscle of transgenic mice in which YFP fluorescence was found in arterial walls of various tissues. In dissociated VSM cells from the mice blue light evoked inward currents, leading to depolarization and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…Depolarization of smooth muscle cells expressing ChR2 by blue light induces vasoconstriction in brain of SM22-ChR2 mice. Recently, it has been reported that contraction of bladder smooth muscles and cardiovascular smooth muscles can be regulated by ChR2 [29,30]. So, we used ChR2 mice to control cerebral vasoconstriction in vivo through optical light stimulation.…”
Section: In Vivo Animal Preparation and Imaging For Optical Activatiomentioning
confidence: 99%
“…Depolarization of smooth muscle cells expressing ChR2 by blue light induces vasoconstriction in brain of SM22-ChR2 mice. Recently, it has been reported that contraction of bladder smooth muscles and cardiovascular smooth muscles can be regulated by ChR2 [29,30]. So, we used ChR2 mice to control cerebral vasoconstriction in vivo through optical light stimulation.…”
Section: In Vivo Animal Preparation and Imaging For Optical Activatiomentioning
confidence: 99%
“…Thus, opening of ChR2 channels typically leads to cell membrane potential ( V m ) depolarization (Nagel et al ., ; Caldwell et al ., ; Lin, ). Several ChR2 variants have been generated, including ChR2(H134R), characterized by reduced current desensitization and enhanced photocurrents as a consequence of the replacement of histidine at position 134 by arginine (Nagel et al ., ; Lin, ; Reinbothe et al ., ; Bruegmann et al ., ; Wu et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…An advance in this direction was recently made by Wu et al . (), who selectively expressed a ChR2 mutant in murine vascular smooth muscle cells (VSMCs) to achieve optogenetic control of VSMC contraction and hence arterial tone. In their study, isolated aortic VSMCs expressing ChR2 channels demonstrated blue light‐induced currents.…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggest that optogenetics can be applied for the treatment of LUT dysfunctions such as OAB and DUA. It has been recently reported that contraction of blood vessels can be also regulated by ChR224.…”
Section: Discussionmentioning
confidence: 99%